Ionic liquid-enhanced lemon biomass carbon dots with sustainable use in bionic antibody microspheres for urea capture and ethyl carbamate inhibition. (30th July 2023) - Meng, Chen; Xie, Chenchen; He, Jingbo; Chen, Xiaolin; Liu, Huilin; Sun, Baoguo
Highlights: Ionic liquid-enhanced lemon biomass CDs encapsulated in bionic antibodies was prepared. Imidazole ILs and lemon rich in heteroatoms to enhance fluorescence intensity of CDs. IL-modified CDs@BAs showed good selectivity and capture toward urea. The inhibition rate of EC by urea route was 29.07 % by using IL-modified CDs@BAs. Abstract: Herein, we reported the room-temperature fabrication of ionic liquid-modified carbon dots encapsulated in bionic antibodies (IL-modified CDs@BAs) by one-pot green synthesis. In order to enhance the fluorescence intensity of CDs, imidazole ILs and lemon rich in heteroatoms were selected as CDs modifiers and sources. The resulting IL-modified CDs@BAs showed good selectivity and capture toward urea and obviously induced fluorescence quenching by template-binding. The inhibition rate ofIL-modified CDs@BAs on the urea pathway of ethyl carbamate was about 29.07% in the simulated Huangjiu system, indicating a good inhibitory effect. The IL-modified CDs@BAs system was also reproducible after five consecutive uses, thus reducing the economic cost. This research would expand the application fields of BAs-based optical sensing system from the perspectives of energy conservation, environmental protection and resource recovery, focusing on their application in the field of food safety control.